EFEKTIVITAS PEMBELAJARAN ONLINE MENGGUNAKAN GOOGLE CLASSROOM SELAMA PANDEMI COVID-19 PADA MATA PELAJARAN AGAMA HINDU - I Kadek Arta Jaya; Ni Wayan Arsini (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
The purpose of this study was to determine the effectiveness of online learning using google classroom during the Covid-19 epidemic in Hinduism. This research is a quantitative descriptive study that focuses on evaluating online learning using google classroom. The population of this study were all students of SMK Negeri 5 Denpasar who were taught Hinduism online using google classroom. The sample of this research was the students of class XII AP1 of SMK Negeri 5 Denpasar which were selected by random sampling technique by considering the homogeneity of the population. Instruments in data collection using online learning questionnaires. Data analysis used descriptive statistical analysis. The results showed that students rated Hinduism learning online using google classroom as much as 23.30%, most students rated it as effective as 46.70%, and students rated it as normal as much as 20.00%. Although there are also students who rate online/online learning using Google Calssroom as less effective as much as 10.00%, and also absolutely no 0.00% who rate it as very ineffective. To be able to improve the quality of online Hindu religious learning during the Covid-19 pandemic, educators are required to fulfill ten suggestions from students, namely (1) a more concise description of learning materials; (2) The selection of material in the video must be based on the criteria of language that is easy to understand; (3) Minimizing the delivery of heavy video material to save quota; (4) Learning is done through video calls; (5) Giving various and different questions for each student; (6) Continue to provide material before the assignment; (7) The assignment must include the working method; (8) Remind students if there is an assignment given; (9) Giving assignments according to the lesson schedule; and (10) Reduce tasks.